Managing Stress During Long-Term Internships: What Coping Strategies Matter and Can a Workbook Help? - Hanna-Sophie Homann; Timo Ehmke (Education Sciences)
The unique demands of teaching contribute to elevated stress levels among educators worldwide. Equipping teachers with adaptive coping skills is increasingly important. However, there is a gap in understanding which coping strategies are essential for pre-service teachers and how universities can best promote them. This study examines pre-service teachers’ coping strategies during a long-term internship and evaluates a low-threshold intervention to enhance stress management and self-care. Three seminar groups were randomly assigned to the experimental group (n = 54), while the remainder formed the control group (n = 119). The experimental group received a self-directed workbook at the start of their internship and three brief face-to-face sessions during accompanying seminars. The workbook modules and seminars guided the pre-service teachers in identifying stressors, developing coping skills, and utilizing personal resources. Data were collected before and after the 18-week internship, measuring well-being, internship-related stressors, and coping strategies. Structural equation modeling showed that positive self-instruction and rumination significantly predicted well-being at the internship’s end, reducing or increasing stress from the internship. Despite the positive response of the pre-service teachers, the workbook did not have an impact. However, the results provide clear implications for the design of future interventions in this area. This study highlights the need for universities to integrate stress management into their curricula.